한국산 물푸레나무屬 주요 수종의 물리 및 역학적 특성 - 권구중; 김남훈; 황원중 (목재공학, 30(2), 2002)
물푸레나무속 주요 수종의 합리적 이용을 위한 기초 자료를 얻기 위해, 물리 및 역학적 특성을 조사하였다. 물푸레나무와 쇠물푸레의 생재함수율은 변·심재간 차이가 없었으나, 들메나무 심재부의 생재함수율은 변재부보다 다소 높았다. 들메나무의 생재밀도와 전건밀도는 다른 두 수종에 비해 낮게 나타났고, 쇠물푸레 변재부의 수축·팽윤율은 물푸레나무보다 다소 높은 값을 보여주었다. 쇠물푸레의 종압축강도와 종압축탄성계수는 다른 두 수종보다 다소 낮았으며, 쇠물푸레 방사·접선단면의 전단강도는 다른 두 수종보다 높게 나타났고, 세 수종 모두 방사단면 전단강도가 접선단면보다 높았다. 세 수종 모두 우수한 휨 특성을 나타냈다. 물푸레나무와 들메나무간에 있어서 충격휨흡수에너지는 유의적인 차이가 없었다. Physical and mechanical properties of major Korean ash species were examined. For Fraxinus rhynchophylla and Fraxinus sieboldiana, green moisture content of sapwood was almost the same value as heartwood. Heartwood of Fraxinus mandshurica, however, had slightly higher moisture content than sapwood. Green and oven dry densities of F. mandshurica were lower than those of F. rhynchophylla and F. sieboldiana. Swelling and shrinkage of sapwood in F. sieboldiana showed somewhat higher value than those of F. rhynchophylla. Longitudinal compressive strength and modulus of elasticity in F. sieboldiana were lower values than those in the other species. Shearing strength in radial section was higher than that in tangential section of all samples. It could be noted that shearing strength of F. sieboldiana demonstrated higher value than that of the other species. Three species had excellent bending properties in MOR and MOE. Impact bending absorbed energy for F. rhynchophylla and F. mandshurica did not show any significant differences. KCI Citation Count: 2